Crosstalk Between Retinoic Acid and Sex-Related Genes Controls Germ Cell Fate and Gametogenesis in Medaka - Adolfi, Mateus C.; Herpin, Amaury; Martinez-Bengochea, Anabel; Kneitz, Susanne; Regensburger, Martina; Grunwald, David J.; Schartl, Manfred (Frontiers in Cell and Developmental Biology, 2021)
Sex determination (SD) is a highly diverse and complex mechanism. In vertebrates one of the first morphological differences between the sexes is the timing of initiation of the first meiosis, where its initiation occurs first in female and later in male. Thus, SD is intimately related to the responsiveness of the germ cells to undergo meiosis in a sex-specific manner. In some vertebrates, it has been reported that the timing for meiosis entry would be under control of retinoic acid (RA), through activation of Stra8. In this study, we used a fish model species for sex determination and lacking the stra8 gene, the Japanese medaka (Oryzias latipes), to investigate the connection between RA and the sex determination pathway. Exogenous RA treatments act as a stress factor inhibiting germ cell differentiation probably by activation of dmrt1a and amh. Disruption of the RA degrading enzyme gene cyp26a1 induced precocious meiosis and oogenesis in embryos/hatchlings of female and even some males. Transcriptome analyzes of cyp26a1 -/- adult gonads revealed upregulation of genes related to germ cell differentiation and meiosis, in both ovaries and testes. Our findings show that germ cells respond to RA in a stra8 independent model species. The responsiveness to RA is conferred by sex-related genes, restricting its action to the sex differentiation period in both sexes.